2021
DOI: 10.1001/jamanetworkopen.2021.1020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Compassion Cultivation Training Program for Caregivers of People With Mental Illness in Denmark

Abstract: Key Points Question Is a compassion cultivation training (CCT) intervention effective in decreasing psychological distress in informal caregivers of people with mental illness? Findings In this randomized clinical trial including 161 caregivers randomized to a CCT program or waitlist group, caregivers who received CCT experienced significant improvements in depression, anxiety, and stress, and the improvements were maintained at 6-month follow-up. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…The action theory describes how the intervention is supposed to affect the mediators. Our effectiveness trial supported the action theory as it showed statistically significant effects of CCT on mindfulness, self-compassion, and emotion regulation ( 12 ). Our predefined conceptual theory was based on the Process Model of Emotion Regulation developed by Gross and John ( 16 ).…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…The action theory describes how the intervention is supposed to affect the mediators. Our effectiveness trial supported the action theory as it showed statistically significant effects of CCT on mindfulness, self-compassion, and emotion regulation ( 12 ). Our predefined conceptual theory was based on the Process Model of Emotion Regulation developed by Gross and John ( 16 ).…”
Section: Introductionsupporting
confidence: 63%
“…The current study design is a longitudinal path model in an RCT. This is a secondary mediation analysis of a published RCT ( 12 ) comparing a CCT intervention to a waitlist control group for informal caregivers of people with a mental illness. Details of the RCT and adherence to the Consolidated Standards of Reporting Trials (CONSORT) reporting guidelines have been reported previously ( 12 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations